The role of interest in Islamic financial transactions - Abdul Samad, Aida Syazwana; Mohd Zanawawi, Norsyamin Nadira; Nor Azmi, Nurul Nabila; Auzar, Nurul Iffah Nadzirah; Saipul Bahrin, Ra'isah Syadiah (2025)
In Islamic finance, the concept of maslahah is one of the key principles taken into consideration when determining the necessity of any transaction. Maslahah refers to the benefit recognised by Islamic law, which aims to protect human interests and ward off harm. It is an important basis for ensuring that Islamic financial products and practices not only meet Sharia requirements, but also deliver real benefits to society, the economy and the nation (Mohd S, n.d.). The discussion of maslahah cannot be separated from the concept of maqasid al-sharia, which are the main objectives to be achieved through the application of Islamic law. Maqasid al-sharia includes the preservation of five basic things, namely religion, life, mind, progeny and wealth. To achieve this goal, scholars have classified human needs into three levels: necessity, need and improvement. Every Islamic financial transaction based on maslaha must take these three levels into account to ensure that it delivers real overall benefits to the user and does not conflict with the principles of Sharia. (2011, Othman R). Therefore, this paper will discuss in depth the concept of maslahah in Islam and its relationship to the objectives of Shariah, followed by an analysis of the role of maslahah in the context of Islamic finance. It will also address the application of maslahah in various Islamic financial instruments and highlight contemporary issues that arise in its application. Finally, it will highlight several suggestions for addressing these challenges in order to ensure the continuity and effectiveness of the concept of maslahah in the current Islamic financial system.